A new study of technology management - Yamanouchi, Teruo (Asian Productivity Organization, 1995)
This in-depth analysis examiness the demands that technology and innovation present to business, outtines strategies and techniques to meet these demands, provides insight into the human factors involved in technological innovation, and proposes an image of corporate management for a new age.